2020
DOI: 10.1016/j.acha.2019.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on CUR decompositions

Abstract: The CUR decomposition is a factorization of a low-rank matrix obtained by selecting certain column and row submatrices of it. We perform a thorough investigation of what happens to such decompositions in the presence of noise. Since CUR decompositions are non-uniquely formed, we investigate several variants and give perturbation estimates for each in terms of the magnitude of the noise matrix in a broad class of norms which includes all Schatten p-norms. The estimates given here are qualitative and illustrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…It also illustrates its relationship with the CUR decomposition studied e.g. by Mahoney and Drineas in [13], Wang and Zhang [28], Sorensen and Embree [21], Hamm and Huang [8], and predicted by Penrose in [19].…”
Section: Related Workmentioning
confidence: 69%
See 1 more Smart Citation
“…It also illustrates its relationship with the CUR decomposition studied e.g. by Mahoney and Drineas in [13], Wang and Zhang [28], Sorensen and Embree [21], Hamm and Huang [8], and predicted by Penrose in [19].…”
Section: Related Workmentioning
confidence: 69%
“…As demonstrated by Nakatsukasa, the preferred way to compute the mixing matrix, G = (Ω * r AΩ c ) + , is to perform a QR factorization Ω * r AΩ c = QR and then take Wang and Zhang [28], Martinsson and Tropp [14], Hamm and Huang [8], and others.…”
Section: Generalized Nyström's Methods and The Cur Decompositionmentioning
confidence: 99%
“…For the reader's convenience, we recall the following characterization of CUR decompositions of low-rank matrices given in [20].…”
Section: Characterization Of Cur Decompositionsmentioning
confidence: 99%
“…Note that if C and R are column and row submatrices of A which has low-rank, and U is the matrix formed from entries where C and R overlap -i.e., if C = A(:, J) and R = A(I, :) then U := A(I, J)then the classical statement of the CUR decomposition is that A = CU † R if and only if rank (U ) = rank (A). This exact decomposition goes back at least as far as the 1950s [24] in the case that U is square and invertible (this case also follows from rank additivity for Schur decompositions [17]); for a history, the reader is invited to consult [20], but the main theorem therein which characterizes this exact decomposition is restated in Section 3. Our initial sampling result is obtained from some established results of Rudelson and Vershynin [27].…”
mentioning
confidence: 99%
“…This enforced structure makes the bases, a.k.a. singular vectors, hard to interpret [9]. On the other hand, it is shown that borrowing bases from the actual samples of a dataset provides a robust representation, which can be employed in interesting applications where sampling is their key factor [20].…”
Section: Introductionmentioning
confidence: 99%